2009
DOI: 10.4161/cc.8.19.9751
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MKP-1 and Bcl-2 in acquired cisplatin resistance in ovarian cancer cells

Abstract: Although cisplatin is a very effective anticancer agent against several types of cancer including ovarian cancer, the mechanisms of acquired resistance are not fully understood. By chronically exposing cisplatin to ovarian cancer cell lines, we established two cisplatin-resistant cell lines OV433 and tOV112D. Our results indicate that the mechanisms underlying their cisplatin resistance are distinct. In OV433 cells, cisplatin resistance is associated with increased expression of mitogen-activated protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 35 publications
5
38
0
Order By: Relevance
“…It has been reported that altered expression and activation of genes involved in cell death pathways were involved in the cisplatin resistance (Galluzzi et al, 2012). A recent study showed the activity of BCL-2 which is an anti-apoptosis protein contributed to the cisplatin resistance in chondrosarcoma (Wang et al, 2009). Overexpression of BCL-2 rendered chondrosarcoma cells resistant to cisplatin treatments, while BCL-2 inhibition can reverse chemoresistance of chondrosarcoma in vitro.…”
Section: Microrna-100 Resensitizes Resistant Chondrosarcoma Cells To mentioning
confidence: 99%
“…It has been reported that altered expression and activation of genes involved in cell death pathways were involved in the cisplatin resistance (Galluzzi et al, 2012). A recent study showed the activity of BCL-2 which is an anti-apoptosis protein contributed to the cisplatin resistance in chondrosarcoma (Wang et al, 2009). Overexpression of BCL-2 rendered chondrosarcoma cells resistant to cisplatin treatments, while BCL-2 inhibition can reverse chemoresistance of chondrosarcoma in vitro.…”
Section: Microrna-100 Resensitizes Resistant Chondrosarcoma Cells To mentioning
confidence: 99%
“…MTT Assays-MTT assays were performed as described previously (28). Briefly, cells were left untreated or pretreated with U0126 (10 M), SB203580 (10 M), SP600125 (10 M), or 3-MA (1 mM) for 30 min and then left untreated or treated with cisplatin.…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot Analysis-Cell lysates were prepared as described previously (28), and protein concentration was determined using the Protein Assay Kit (Bio-Rad). Cell lysates were electrophoresed through denaturing polyacrylamide gels and transferred to a PVDF membrane (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysates were prepared as described previously. 31 Briefly, cells were washed twice in ice-cold PBS, and immediately lysed in lysis buffer. Protein concentrations were quantified by a Protein Assay Kit (Biorad), and total proteins (100 μg) were loaded on SDS-PAGE gels, transferred onto polyvinylidene difluoride membrane (Millipore).…”
Section: Methodsmentioning
confidence: 99%